IMPROVING STUDENTS’ READING COMPREHENSION THROUGH STUDENT TEAM ACHIEVEMENT DIVISION OF VIII GRADE AT SMPN 1 GALANG - Jaya, Jaya (Universitas Madako Tolitoli, 2017)
The objective of the research is to prove whether the use of STAD is effective ornot to improve students’ reading comprehension in narrative text. This pre – experimentalresearch use 27 students as a sample. They are Grade VIIIA of SMP NEGERI 1 Galang. Theprocedure of this research consist of pretest, treatment, and posttest. Pretest and posttest aregiven to know the use of STAD can improve students’ reading comprehension or not. The resultof the analysis data show that STAD contribute greatly to the students’ comprehension innarrative text. It can be seen by the difference of the mean score between pretest and posttest.The mean score of pretest is 57.93 while in the posttest improved up to 80.69. the data of thisresearch are analyzed by SPSS Program 16.0. Moreover, the Minimum Mastery Criterion ofEnglish lesson is 75. Then the data of both tests are analyzed by using T-test, and the resultshowed that the T-test value 41.062 is high than T-table value 2.056. It can be inferred thatSTAD method is very effective to improve students’ reading comprehension in narrative text.Keywords: Student, Team Achievement Division, Reading